A short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based wave-absorbing composite material and a preparation method thereof

CN123004083APending Publication Date: 2026-10-30SHANDONG NON METALLIC MATERIAL RESEARCH INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611132477.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明为解决现有技术中制备树脂基吸波复合材料步骤繁琐以及韧性差的问题,进而提出了一种短切碳纤维-镍-多巴胺增强热固性树脂基吸波复合材料及其制备方法

Benefits of technology

(1)本发明制备的短切碳纤维-镍-多巴胺增强热固性树脂基吸波复合材料结合了短切碳纤维轻质、增韧等特点与金属镍的介电损耗、磁损耗等特点,赋予复合材料优良的韧性和高效的电磁波吸收性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004083A_ABST
    Figure CN123004083A_ABST
Patent Text Reader

Abstract

This invention belongs to the technical field of resin-based electromagnetic wave absorbing composite materials. It discloses a short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based electromagnetic wave absorbing composite material and its preparation method. The invention involves surface treatment of short-cut carbon fibers, chemical nickel plating, and coating with a PDA layer to obtain a CF-Ni-PDA material. This material is then mixed with epoxy resin and cured to obtain the short-cut carbon fiber-nickel-dopamine electromagnetic absorbing composite material. Coating the carbon fiber surface with a PDA layer effectively improves the surface roughness of the carbon fiber and enriches its surface with a large number of active functional groups, enhancing the hydrophilicity of the carbon fiber and greatly increasing its uniform dispersion in the resin. Ultimately, this enhances the toughness of the composite material, increasing its flexural strength and tensile strength by 15% and 12%, respectively. Simultaneously, due to the presence of the metallic nickel layer, the composite material exhibits enhanced conductivity and electromagnetic wave absorption performance, effectively absorbing more than half of the X-band electromagnetic waves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of resin-based electromagnetic wave absorbing composite materials, and relates to a wave-absorbing composite material and its preparation method, specifically to a short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based wave-absorbing composite material and its preparation method. Background Technology

[0002] In aerospace, military equipment, and electronic communications, electromagnetic interference (EMI) absorbing composite materials are core materials for achieving equipment stealth and suppressing electromagnetic interference. Short-cut carbon fiber reinforced thermosetting resin-based composites have become the preferred system in this field due to their high specific strength, high specific modulus, corrosion resistance, and controllable EMI absorption performance. Their core lies in constructing a conductive network using short-cut carbon fibers, combined with a stable thermosetting resin structure, to achieve efficient absorption and conversion of electromagnetic waves. However, existing technologies face a key bottleneck: although the short-cut carbon fibers are cut, residual sizing agent on the surface easily leads to fiber adhesion and agglomeration, especially in high-fiber-content formulations, making it extremely difficult to control the uniformity of dispersion. This defect makes it difficult for the resin to fully impregnate the agglomerated fiber bundles, easily forming dry yarns and pores inside, thus deteriorating the material's mechanical properties and failing to meet the stringent structural stability requirements of high-end equipment.

[0003] Patent CN113024995A discloses a high-strength, high-modulus electromagnetic shielding composite material CF-Ni-PDA / CNT / epoxy with carbon fiber fabric as the matrix. However, its preparation process requires surface oxidation treatment of the nickel-plated carbon fiber fabric and the addition of costly CNTs to enhance its shielding performance and material strength, making the preparation process overly complex and costly, which is not conducive to industrial production applications. Patent CN112888287A discloses a method for preparing electromagnetic shielding carbon fiber powder. Its preparation process is complex and not conducive to dispersion in resin. For short-cut carbon fibers in resin, local fiber agglomeration can lead to the breakage of the conductive network, resulting in reduced absorption efficiency and narrower bandwidth. However, traditional dispersion methods are difficult to balance the dispersion effect with fiber damage. Excessive processing intensity can easily lead to secondary breakage of short-cut carbon fibers, further restricting performance improvement.

[0004] Therefore, modifying short-cut carbon fibers to improve their microwave absorption properties and dispersibility in thermosetting resins has become a key technological breakthrough. Summary of the Invention

[0005] This invention addresses the problems of cumbersome preparation steps and poor toughness in existing resin-based microwave absorbing composite materials by proposing a short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material and its preparation method. The invention involves surface treatment of short-cut carbon fibers, electroless nickel plating, and coating with a dopamine (PDA) layer to obtain a CF-Ni-PDA material. This material is then mixed with epoxy resin and cured to obtain the short-cut carbon fiber-nickel-dopamine electromagnetic absorption composite material. Coating the carbon fiber surface with a PDA layer effectively improves the surface roughness and enriches it with numerous active functional groups, enhancing the hydrophilicity of the carbon fibers and significantly increasing their uniform dispersion in the resin. This ultimately enhances the toughness of the composite material, increasing flexural strength and tensile strength by 15% and 12%, respectively. Simultaneously, the presence of the metallic nickel layer enhances the composite material's conductivity and electromagnetic wave absorption performance, effectively absorbing more than half of the X-band electromagnetic waves.

[0006] The specific technical solution of the present invention is as follows: A method for preparing a short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material, the specific steps of which are as follows: (1) Place the short carbon fibers in a nitric acid solution for ultrasonic acid washing for 30-40 min. After the acid washing is completed, filter out the short carbon fibers, wash, filter and dry for later use. Then, put the obtained acid-washed carbon fibers into SnCl2 solution for sensitization treatment. After ultrasonic treatment for 10-15 min, filter, wash and dry. Then, activate the sensitized carbon fibers by placing them in PdCl2 solution and ultrasonicating at room temperature for 10-15 min. After filtration, washing and drying, the pretreated short carbon fibers are obtained. (2) The pretreated carbon fiber obtained in step (1) is ultrasonically dispersed into a chemical nickel plating solution for 10-15 min. After adjusting the pH value of the solution, chemical nickel plating is carried out by stirring in a water bath at 60-80℃. After stirring, the carbon fiber is filtered, washed and dried to obtain nickel-plated carbon fiber. (3) Prepare a Tris solution and adjust its pH value with hydrochloric acid. Then, ultrasonically disperse the nickel-plated carbon fiber obtained in step (2) into the Tris solution for 10-15 min. Add dopamine hydrochloride and stir at room temperature to carry out the polymerization reaction. After the reaction is completed, filter, wash and dry to obtain dopamine-coated nickel-plated short carbon fiber (CF-Ni-PDA) material. (4) Stir and mix epoxy resin, curing agent and acetone at 1400-1600 r / min for 1-2 hours, then add CF-Ni-PDA material obtained in step (3) and continue stirring for 1-2 hours to obtain mixed resin. After vacuum defoaming treatment, pour it into mold and cure it in oven. After curing, demold to obtain short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material.

[0007] Preferably, the washing in steps (1)-(4) is done with deionized water until neutral, and the drying is done at 60°C for 6 hours.

[0008] Preferably, the chopped carbon fiber in step (1) has a diameter of 7 μm and a length of 1-4 mm.

[0009] Preferably, the mass fraction of the nitric acid solution in step (1) is 60%-70%, and the mass-volume ratio of the short-cut carbon fiber to the nitric acid solution is 3-6 g / L.

[0010] Preferably, in step (1) sensitization treatment, the concentration of SnCl2 solution is 10-15 g / L, and the treatment time is 10-15 min; the mass-to-volume ratio of the acid-washed carbon fiber to the SnCl2 solution is 20-30 g / L; in activation treatment, the PdCl2 solution is 0.2-0.5 g / L, and the treatment time is 10-15 min; the mass-to-volume ratio of the acid-washed carbon fiber to the PdCl2 solution is 20-30 g / L.

[0011] The purpose of acid washing in step (1) is to remove impurities from the carbon fiber surface and introduce hydrophilic groups to improve its wettability; the purpose of sensitization treatment is to allow the carbon fiber to adsorb Sn. 2+ The ions will be activated in the next step, transferring Pd ions. 2+ It is reduced to Pd, and Pd is the nickel plating process in step (2) that reduces Ni to Pd. 2+ Catalysts for reduction to Ni.

[0012] Preferably, the electroless nickel plating solution in step (2) is composed of nickel sulfate, sodium hypophosphite, sodium citrate, ammonium chloride, potassium sodium tartrate, and deionized water, wherein nickel sulfate is the nickel source, sodium hypophosphite is the reducing agent, sodium citrate is the complexing agent, ammonium chloride is the stabilizer, and deionized water is the solvent; the concentration of NiSO4 is 20-30 g / L, the concentration of NaH2PO2 is 20-30 g / L, the concentration of C6H5Na3O7 is 20-35 g / L, the concentration of NH4Cl is 15-25 g / L, and the pH of the solution is adjusted to 9-12 with potassium sodium tartrate at a concentration of 15 g / L.

[0013] Preferably, in step (2), the mass-to-volume ratio of the pretreated carbon fiber to the electroless nickel plating solution is 2-4 g / L; the electroless nickel plating time is 1 h.

[0014] Preferably, the concentration of the Tris solution in step (3) is 0.1-0.3 wt%, and the pH value is adjusted to 8.5 using 10% hydrochloric acid.

[0015] Preferably, the mass-to-volume ratio of the nickel-plated carbon fiber to the Tris solution in step (3) is 20-30 g / L.

[0016] Preferably, in step (3), the mass ratio of nickel-plated carbon fiber to dopamine hydrochloride is 20-40:1. The dopamine polymerization time is 20-24h, and the stirring speed is 700-900r / min.

[0017] Preferably, the epoxy resin in step (4) is bisphenol A type, the curing agent is methyltetrahydrophthalic anhydride, the curing temperature is 90-100℃, and the curing time is 6-8 h. The mass ratio of epoxy resin to curing agent is 2:1, and acetone is used as a diluent with no limitation on the proportion added.

[0018] Preferably, in step (4), the CF-Ni-PDA material accounts for 20-35% of the total mass of the resin system (epoxy resin + curing agent + CF-Ni-PDA).

[0019] Furthermore, the present invention also claims protection for the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material obtained by the above preparation method.

[0020] The short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material prepared by the method provided in this invention combines the lightweight and toughening characteristics of short-cut carbon fiber with the electrical and magnetic loss characteristics of metallic nickel. Furthermore, the dopamine layer is coated outside the nickel layer to increase the surface active functional groups of the carbon fiber, which is beneficial for the subsequent interfacial reaction with the resin matrix and improves the dispersion uniformity, thereby endowing the composite material with excellent toughness and efficient electromagnetic wave absorption performance.

[0021] Compared with the prior art, the technical effects achieved by the present invention are as follows: (1) The short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material prepared by the present invention combines the lightweight and toughening characteristics of short-cut carbon fiber with the dielectric loss and magnetic loss characteristics of metallic nickel, giving the composite material excellent toughness and efficient electromagnetic wave absorption performance.

[0022] (2) In this invention, the pretreatment of carbon fibers improves the dispersion of carbon fibers in the electroless nickel plating solution and enhances their affinity for Ni. 2+The reducing properties of carbon fibers, the simple chemical nickel plating method, and the uniform nickel layer enable carbon fibers to possess both dielectric and magnetic loss capabilities, which is beneficial to enhancing the microwave absorption performance of the final composite material.

[0023] (3) The present invention further coats the nickel layer with a dopamine layer, which increases the surface active functional groups of the carbon fiber, which is beneficial to the interface reaction with the resin matrix in the later stage and improves the dispersion uniformity.

[0024] The short-cut carbon fiber / nickel / dopamine-reinforced thermosetting resin-based microwave absorbing composite material prepared by this invention exhibits enhanced mechanical strength due to improved fiber composite material dispersion. Simultaneously, it can effectively absorb half of the X-band electromagnetic waves.

[0025] This invention enhances the hydrophilicity of nickel-plated chopped carbon fiber surfaces, ensuring the fiber forms a continuous conductive network within the resin, optimizing wave absorption performance and broadening the effective frequency band. It also achieves full resin wetting, eliminating internal defects and improving product mechanical properties. Furthermore, this method requires no significant modifications to existing production equipment, balancing process compatibility and feasibility. This facilitates the large-scale application of the material in high-end manufacturing, providing crucial support for the development of lightweight and stealth equipment. Attached Figure Description

[0026] Figure 1 Here is a scanning electron microscope image of the CF-Ni-PDA material prepared in Example 1; Figure 2 Contact angle diagrams of the CF-Ni material prepared in the comparative example and the CF-Ni-PDA material prepared in Example 1 are shown. (a) is the CF-Ni material, and (b) is the CF-Ni-PDA material. Figure 3 The electromagnetic wave absorption performance diagrams of the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material prepared in Example 2 are shown in (a) and (b) respectively. Detailed Implementation

[0027] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but this should not be construed as limiting the technical solution. Any technical method that can implement the present invention constitutes a part of the technical solution of the present invention.

[0028] Example 1: A method for preparing a short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material, the specific steps of which are as follows: (1) Place 2g of short-cut carbon fibers with a diameter of 7μm and a length of 2mm into 400mL of 60% nitric acid solution, and place the beaker in an ultrasonic machine for ultrasonic treatment for 30min. After filtering, wash with deionized water until neutral, filter by suction, and dry at 60℃ for 6 hours for later use; The acid-treated short-cut carbon fibers were sensitized by placing 1.5g of the acid-treated fibers in 50mL of a 10g / L SnCl2 solution and sonicating for 10 minutes. After the treatment, the fibers were filtered, washed three times with deionized water until neutral, and dried at 60°C for 6 hours. Activation treatment was then carried out by placing the sensitized carbon fibers in 50mL of a 0.2g / L PdCl2 solution and sonicating for 10 minutes. After the treatment, the fibers were washed with deionized water until the washing solution was neutral and dried at 60°C for 6 hours to obtain the pretreated short-cut carbon fibers. (2) Prepare a chemical nickel plating solution with NiSO4 concentration of 20 g / L, NaH2PO2 concentration of 20 g / L, C6H5Na3O7 concentration of 20 g / L, NH4Cl concentration of 15 g / L, and deionized water as solvent. Disperse the pretreated carbon fiber (0.4 g) obtained in step (1) into the chemical nickel plating solution (200 mL) by ultrasonication for 30 min. Adjust the pH of the solution to 9 with 15 g / L potassium sodium tartrate. Stir in a 60 °C water bath for 1 hour. After stirring, filter and wash with deionized water until the washing solution is neutral. Dry at 60 °C for 6 hours to obtain nickel-plated carbon fiber. (3) Prepare 200 mL of Tris buffer solution with a concentration of 0.1 wt%, adjust the pH value to 8.5 with 10% dilute hydrochloric acid, put 6 g of nickel-plated carbon fiber into the Tris solution, sonicate for 10 min, add 0.15 g of dopamine hydrochloride and stir and polymerize at room temperature for 20 hours at a stirring speed of 800 r / min. After the reaction is completed, filter, wash with deionized water until the washing liquid is neutral, and dry at 60°C for 6 hours to obtain dopamine-coated nickel-plated short carbon fiber CF-Ni-PDA material; (4) Mix 6g of bisphenol A epoxy resin, 3g of methyltetrahydrophthalic anhydride curing agent and 1g of acetone. After mechanically stirring at 1500 r / min for 1 hour, mix in 2.5g of CF-Ni-PDA material and continue stirring for 2 hours to obtain a mixed resin. Place the mixed resin in a vacuum device for defoaming treatment until there are no bubbles on the surface of the mixed resin. Pour it into a mold and cure it in a 90℃ oven for 6 hours to obtain the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material.

[0029] Example 2: A method for preparing a short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material, the specific steps of which are as follows: (1) The acidification treatment of short carbon fibers is the same as in Example 1. Take 1.2g of acidified short carbon fibers and sensitize them. Place them in 50mL of SnCl2 solution with a concentration of 15g / L and sonicate for 15 minutes. After the treatment, filter them and wash them three times with deionized water until neutral. Dry them at 60°C for 6 hours. Continue to activate the carbon fibers. Place the sensitized carbon fibers in 50mL of PdCl2 solution with a concentration of 0.4g / L and sonicate for 15 minutes. After the treatment, wash them with deionized water until the washing solution is neutral. Dry them at 60°C for 6 hours to obtain the pretreated short carbon fibers. (2) Prepare a chemical nickel plating solution with NiSO4 concentration of 25 g / L, NaH2PO2 concentration of 30 g / L, C6H5Na3O7 concentration of 25 g / L, NH4Cl concentration of 20 g / L, and deionized water as solvent. Disperse the pretreated carbon fiber (0.4 g) obtained in step (1) into the chemical nickel plating solution (200 mL) by ultrasonication for 30 min. Adjust the pH value to 10 with 15 g / L of potassium sodium tartrate. Stir in a 60°C water bath for 1 hour. After stirring, filter and wash with deionized water until the washing solution is neutral. Dry at 60°C for 6 hours to obtain nickel-plated carbon fiber. (3) Prepare 200 mL of Tris solution with a concentration of 0.2 wt%, adjust the pH value to 8.5 with 10% dilute hydrochloric acid, put 6 g of nickel-plated carbon fiber into the Tris solution, sonicate for 10 min, add 0.2 g of dopamine hydrochloride, stir and polymerize at room temperature for 20 hours at a stirring speed of 800 r / min, filter after the reaction, wash with deionized water until the washing liquid is neutral, dry at 60℃ for 6 hours to obtain dopamine-coated nickel-plated short carbon fiber CF-Ni-PDA material; (4) Mix 6g of bisphenol A type epoxy resin, 3g of methyltetrahydrophthalic anhydride curing agent and 1g of acetone. After mechanically stirring at 1500 r / min for 1 hour, mix in 3.5g of CF-Ni-PDA material and continue stirring for 2 hours to obtain a mixed resin. Place the mixed resin in a vacuum device for defoaming treatment until there are no bubbles on the surface of the mixed resin. Pour it into a mold and cure it in a 90℃ oven for 6 hours to obtain the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material.

[0030] Example 3: A method for preparing a short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material, the specific steps of which are as follows: (1) The acidification treatment of short carbon fibers is the same as in Example 1. Take 1g of acidified short carbon fibers and sensitize them. Place them in 50mL of SnCl2 solution with a concentration of 15g / L and sonicate for 15 minutes. After the treatment, filter them and wash them three times with deionized water until they are neutral. Dry them at 60°C for 6 hours. Continue to activate the carbon fibers. Place the sensitized carbon fibers in 50mL of PdCl2 solution with a concentration of 0.5g / L and sonicate for 15 minutes. After the treatment, wash them with deionized water until the washing solution is neutral. Dry them at 60°C for 6 hours to obtain the pretreated short carbon fibers. (2) Prepare a chemical nickel plating solution with NiSO4 concentration of 30 g / L, NaH2PO2 concentration of 30 g / L, C6H5Na3O7 concentration of 30 g / L, NH4Cl concentration of 25 g / L, and deionized water as solvent. Disperse the pretreated carbon fiber (0.8 g) obtained in step (1) into the chemical nickel plating solution (200 mL) by ultrasonication for 30 min. Adjust the pH value to 10 with 15 g / L potassium sodium tartrate. Stir in a 60 °C water bath for 1 hour. After stirring, filter and wash with deionized water until the washing solution is neutral. Dry at 60 °C for 6 hours to obtain nickel-plated carbon fiber. (3) Prepare 200 mL of 0.3 wt% Tris solution, adjust the pH value to 8.5 with 10% dilute hydrochloric acid, put 6 g of nickel-plated carbon fiber into the Tris solution, sonicate for 10 min, add 0.3 g of dopamine hydrochloride, stir and polymerize at room temperature for 20 hours at a stirring speed of 800 r / min; after the reaction is completed, filter, wash with deionized water until the washing solution is neutral, dry at 60℃ for 6 hours to obtain dopamine-coated nickel-plated short carbon fiber CF-Ni-PDA material; (4) Mix 6g of bisphenol A epoxy resin, 3g of methyltetrahydrophthalic anhydride curing agent and 1g of acetone. After mechanically stirring at 1500 r / min for 1 hour, mix in 4.8g of CF-Ni-PDA material and continue stirring for 2 hours to obtain a mixed resin. Place the mixed resin in a vacuum device for defoaming treatment until there are no bubbles on the surface of the mixed resin. Pour it into a mold and cure it in a 90℃ oven for 8 hours to obtain the short-cut carbon fiber / nickel / dopamine reinforced thermosetting resin-based microwave absorbing composite material.

[0031] A comparative example of a method for preparing a short-cut carbon fiber-nickel-reinforced thermosetting resin-based microwave absorbing composite material, the specific steps of which are as follows: The difference from Example 2 is that the dopamine coating treatment is not performed. After obtaining the CF-Ni material, it is mixed with resin and cured. The remaining steps are the same as in Example 2.

[0032] Figure 1The image shows a scanning electron microscope (SEM) image of the CF-Ni-PDA material prepared in Example 1. It can be seen from the image that the nickel layer is uniformly wrapped around the surface of a single fiber, with a coating thickness of about 1 μm. The metal layer is continuous and uniform, indicating that this electroless plating method can obtain a complete metal layer.

[0033] Figure 2 The contact angle diagrams of the CF-Ni material prepared in comparison with the CF-Ni-PDA material prepared in Example 1 are shown. In (a), the contact angle of the CF-Ni material is 121°, and in (b), the contact angle of the CF-Ni-PDA material is 71°. By comparison, it can be seen that after coating with the PDA layer, the surface functional groups increase and the hydrophilicity improves, which is more conducive to the uniform dispersion of the CF-Ni-PDA material in the resin, thereby increasing the mechanical properties of the final resin-based composite material.

[0034] Figure 3 The electromagnetic wave absorption performance of the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material prepared in Example 2 is shown in Figure 2. The absorption performance was tested using the waveguide method, with a test range of 8.2-12.2 GHz. (a) is a three-dimensional reflection loss diagram; (b) is a two-dimensional reflection loss diagram. As can be seen from the figures, the maximum reflection loss value of the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material is -20.8 dB, and the maximum response bandwidth is 2.2 GHz when the thickness is 1.7 mm. By adjusting its thickness, it can effectively absorb electromagnetic waves in the entire X-band.

[0035] Table 1 shows a comparison of the mechanical properties of the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composites prepared in Examples 1-3 and the comparative examples.

[0036] Table 1. Test data of mechanical properties of composite materials prepared in Examples 1-3 and comparative examples. .

[0037] By comparing the flexural and tensile strengths of the three embodiments and comparative examples, it can be found that coating the surface with dopamine is beneficial to improving toughness. The improved toughness indicates a stronger interfacial bond between the fiber material and the resin, and the more uniform dispersion of the fibers in the resin maximizes the expression of the inherent physical properties of the fibers. Furthermore, the improved fiber dispersion leads to a more complete conductive network structure within the resin. Combined with the good conductivity and magnetism of the nickel coating, this results in the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material exhibiting excellent electromagnetic wave absorption performance.

[0038] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent substitutions, and improvements made to the above embodiments without departing from the scope of the present invention, based on the technical essence of the present invention and within the spirit and principles of the present invention, shall still fall within the protection scope of the present invention.

Claims

1. A method for preparing a short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material, characterized in that, The specific steps are as follows: (1) Place the short carbon fibers in a nitric acid solution for ultrasonic acid washing for 30-40 minutes. After the acid washing is completed, filter out the short carbon fibers, wash, filter and dry for later use. Then, put the obtained acid-washed carbon fibers into SnCl2 solution for sensitization treatment. After ultrasonic treatment for 10-15 minutes, filter, wash and dry. Then, activate the sensitized carbon fibers by placing them in PdCl2 solution and ultrasonicating at room temperature for 10-15 minutes. After filtration, washing and drying, the pretreated short carbon fibers are obtained. (2) The pretreated carbon fiber obtained in step (1) is ultrasonically dispersed into a chemical nickel plating solution for 10-15 minutes. After adjusting the pH value of the solution, chemical nickel plating is carried out by stirring in a water bath at 60-80℃. After stirring, the carbon fiber is filtered, washed and dried to obtain nickel-plated carbon fiber. (3) Prepare a Tris solution and adjust its pH value with hydrochloric acid. Then, ultrasonically disperse the nickel-plated carbon fiber obtained in step (2) into the Tris solution for 10-15 minutes. Add dopamine hydrochloride and stir at room temperature to carry out the polymerization reaction. After the reaction is completed, filter, wash and dry to obtain nickel-plated short carbon fiber material coated with dopamine. (4) Stir and mix epoxy resin, curing agent and acetone at 1400-1600 r / min for 1-2 hours, then add the dopamine-coated nickel-plated short carbon fiber material obtained in step (3), and continue stirring for 1-2 hours to obtain mixed resin. After vacuum defoaming treatment, pour it into mold and cure it in oven. After curing, demold to obtain short carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material.

2. The method for preparing the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material according to claim 1, characterized in that, The washing described in steps (1)-(4) is done with deionized water until neutral, and the drying is done at 60°C for 6 hours.

3. The method for preparing the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material according to claim 1, characterized in that, The short-cut carbon fiber mentioned in step (1) has a diameter of 7μm and a length of 1-4mm.

4. The method for preparing the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material according to claim 1, characterized in that, The nitric acid solution has a mass fraction of 60%-70%, and the mass-to-volume ratio of the short-cut carbon fibers to the nitric acid solution is 3-6 g / L.

5. The method for preparing the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material according to claim 1, characterized in that, In step (1), during the sensitization treatment, the concentration of SnCl2 solution is 10-15 g / L, and the treatment time is 10-15 min; the mass-to-volume ratio of the acid-washed carbon fiber to the SnCl2 solution is 20-30 g / L; during the activation treatment, the concentration of PdCl2 solution is 0.2-0.5 g / L, and the treatment time is 10-15 min; the mass-to-volume ratio of the acid-washed carbon fiber to the PdCl2 solution is 20-30 g / L.

6. The method for preparing the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material according to claim 1, characterized in that, The electroless nickel plating solution in step (2) consists of nickel sulfate, sodium hypophosphite, sodium citrate, ammonium chloride, potassium sodium tartrate, and deionized water. Nickel sulfate is the nickel source, sodium hypophosphite is the reducing agent, sodium citrate is the complexing agent, ammonium chloride is the stabilizer, and deionized water is the solvent. The concentrations of NiSO4, NaH2PO2, C6H5Na3O7, and NH4Cl are 20-30 g / L, 20-35 g / L, and 15-25 g / L. The pH of the solution is adjusted to 9-12 using potassium sodium tartrate at a concentration of 15 g / L.

7. The method for preparing the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material according to claim 1, characterized in that, In step (2), the mass-to-volume ratio of the pretreated carbon fiber to the electroless nickel plating solution is 2-4 g / L, and the electroless nickel plating time is 1 h.

8. The method for preparing the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material according to claim 1, characterized in that, In step (3), the concentration of the Tris solution is 0.1-0.3wt%, and the pH value is adjusted to 8.5 using 10% dilute hydrochloric acid. The mass-volume ratio of the nickel-plated carbon fiber to the Tris solution is 20-30g / L, and the mass ratio of the nickel-plated carbon fiber to dopamine hydrochloride is 20-40:

1. The dopamine polymerization time is 20-24h, and the stirring speed is 700-900r / min.

9. The method for preparing the short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material according to claim 1, characterized in that, The epoxy resin in step (4) is bisphenol A type, the curing agent is methyltetrahydrophthalic anhydride, the curing temperature is 90-100℃, and the curing time is 6-8 h; the mass ratio of epoxy resin to curing agent is 2:1, and acetone is used as a diluent; the CF-Ni-PDA material accounts for 20-35% of the total mass of the resin system, and the resin system includes epoxy resin, curing agent, and CF-Ni-PDA.

10. A short-cut carbon fiber-nickel-dopamine reinforced thermosetting resin-based microwave absorbing composite material obtained by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of electromagnetic shielding material

    CN112888287A

  • High-strength high-modulus electromagnetic shielding function structure integrated light material and preparation method thereof

    CN113024995A